Edukasi Literasi Keuangan Rumah Tangga Melalui Self Awareness Pada Masyarakat Komunitas Sanggar Pelita, Kec. Deli Tua - Rana Fathinah Ananda; Sari Nuzullin Rahmadhani; Anggi Tri Lestari Purba (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Financial literacy is a series of processes or activities to increase consumer knowledge, skills and public confidence in better managing personal finances. Sanggar Pelita, Deli Tua District, is one of the communities. In fact, financial literacy is a 21st century life skill that must be mastered by individuals and society in order to achieve a better standard of living. This community service activity aims to equip housewives with financial literacy so that family financial resilience is realized. The implementation method is counseling accompanied by interactive discussions. The target is the housewives of the Deli Tua District. The problem that arose during the discussion was the problem of attitudes and financial behavior of housewives and their children in the form of excessive spending behavior, not understanding proper financial planning, and not understanding the priority scale of primary, secondary and tertiary needs. The team provides solutions regarding the correct meaning of money, discipline in saving, and the need to make proper financial planning in order to achieve individual and family financial security. This activity has opened the minds and awareness of housewives on the importance of financial literacy in family life. Because financial literacy is the basis for building family financial resilience.